2018
DOI: 10.1371/journal.pone.0201157
|View full text |Cite
|
Sign up to set email alerts
|

Readers and their roles: Evidence from readers of contemporary fiction in the Netherlands

Abstract: Reading serves many ends. Some readers report that works of fiction provide an imaginative escape from the rigors of life, others report reading in order to be intellectually challenged. While various characterizations of readers’ engagement with prose fiction have been proposed, few have been checked using representative samples of readers. Our research reports on reader self-descriptions observed in a representative sample of 501 adults in the Netherlands. Reader self-descriptions exhibit regularities, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…Previous research found that the different dimensions of reading motivation triggered differences in reading speed, comprehension, and conclusion skills (McGeown et al, 2015). A previous study also found that certain readers pay attention to plot structure or read, in order to be intellectually challenged (Riddell & Van Dalen-Oskam, 2018). This study also confirms the result obtained by Riddell & Van Dalen-Oskam (2018) and McGeown et al (2015).…”
Section: Research Paperssupporting
confidence: 84%
“…Previous research found that the different dimensions of reading motivation triggered differences in reading speed, comprehension, and conclusion skills (McGeown et al, 2015). A previous study also found that certain readers pay attention to plot structure or read, in order to be intellectually challenged (Riddell & Van Dalen-Oskam, 2018). This study also confirms the result obtained by Riddell & Van Dalen-Oskam (2018) and McGeown et al (2015).…”
Section: Research Paperssupporting
confidence: 84%
“…Further exploration of the variation between readers could perhaps shine a light on different types of readers that may react differently to aesthetic experiences. For example, it would be interesting to answer the question whether there are mainly cognitively driven (i.e., distanced) or mainly affectively driven (i.e., identifying) readers, as well as readers who are somewhere in between (Riddell & van Dalen-Oskam, 2018 ). In a future experiment studying why participants differ in their routes to liking, it would be interesting to let participants read and rate a larger number of texts (perhaps also including texts of different genres).…”
Section: Discussionmentioning
confidence: 99%
“…(382) Although there are certainly examples of studies in this vein (research within or bordering computational publishing studies have been carried out by e.g. [6,[14][15][16][17][18]; cf. [12], an overwhelming majority of the studies in the field are qualitative.…”
Section: Debates In Digital Publishing Studiesmentioning
confidence: 99%
“…If we look only Table 2 Genre proportions in the dataset per title The category of "crime fiction" in this study follows the bibliography of Swedish crime fiction compiled by the Swedish Crime Fiction Academy (cf. [25], [13][14][15][16][17]. Counted as "prestige fiction" are all books that have been nominated for or awarded a major literary prize (here operationalized as the Nobel Prize in literature, the Pulitzer Prize, The Man Booker Prize, and the two most important literary prizes in a Swedish context: Augustpriset and Nordiska rådets litteraturpris).…”
Section: Popularity Seen As Finished Streamsmentioning
confidence: 99%